Diseño e implementación de la herramienta informática gerencial para el seguimiento y control de la gestión administrativa financiera en base al cuadro de mando integral por programas en base a la ejecución presupuestaria de la Universidad de las Fuerzas Armadas ESPE, año 2014 - Narváez Navarro, Vera Lucía (2014)
The contribution of this work is of benefit to the Universidad de las Fuerzas Armadas ESPE to improve the percentage of annual budget execution as public sector entities are accountable through annual reports on the administration, and the fulfillment of the objectives proposed so as to increase the number of research projects and links with society and be an efficient institution, which is why it is proposed thesis topic: "Design and Implementation of Information Management Tool for Monitoring and Control Administrative Financial Management based on the Balanced Scorecard on Budget Execution of the Universidad de las Fuerzas Armadas - ESPE, 2014 ". With the implementation of the software tool you can perform regular and easy access and interpret assessments so that managers will be in the capacity of decision making for the redistribution of the budget in new activities and projects required and necessary for the institution.